2011
DOI: 10.1371/journal.pgen.1001356
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread Hypomethylation Occurs Early and Synergizes with Gene Amplification during Esophageal Carcinogenesis

Abstract: Although a combination of genomic and epigenetic alterations are implicated in the multistep transformation of normal squamous esophageal epithelium to Barrett esophagus, dysplasia, and adenocarcinoma, the combinatorial effect of these changes is unknown. By integrating genome-wide DNA methylation, copy number, and transcriptomic datasets obtained from endoscopic biopsies of neoplastic progression within the same individual, we are uniquely able to define the molecular events associated progression of Barrett … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 43 publications
9
95
1
1
Order By: Relevance
“…We used a Zeiss stereomicroscope under 60ϫ magnification for the microdissection. Genomic DNA was isolated using the dialysis tubing method, as performed and described previously (13). RNA was extracted using Qiagen RNeasy mini kits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a Zeiss stereomicroscope under 60ϫ magnification for the microdissection. Genomic DNA was isolated using the dialysis tubing method, as performed and described previously (13). RNA was extracted using Qiagen RNeasy mini kits.…”
Section: Methodsmentioning
confidence: 99%
“…cancer can be accomplished via gene amplifications, as well as by aberrant epigenetic modifications (13). Analysis of our integrative CCRCC data set revealed that even though hypermethylation was the predominant epigenetic abnormality in CCRCC (8), JAG1 was one of the select genes that was aberrantly hypomethylated in CCRCC (supplemental Table S1).…”
Section: Integrative Analysis Of Copy Number Alterations and Cytosinementioning
confidence: 99%
“…Genome-wide DNA Methylation Analysis Using the HELP Assay-Genomic DNA was isolated by phenol chloroform extraction, as performed before (9). HELP was carried out as described previously (10).…”
Section: Primary Human Erythroid Cultures and Flow Cytometry-cd34mentioning
confidence: 99%
“…Notably, methylation panels of the aforementioned genetic loci are currently being clinically used as biomarkers of EAC in certain high volume centers [23]. Interestingly, hypomethylation of noncoding DNA regions have been correlated with disease progression as well [24]. Last but not least, investigations regarding the role of microRNAs (miRNAs) in EC are also gaining traction.…”
Section: Discussionmentioning
confidence: 99%